Reciprocal Q/A Presentation: What It Means to the Students - Furqonul Azies (University of Muhammadiyah Purwokerto, 2018)
This study explores (1) students’ perception of the implementation of ‘Reciprocal Q/A Presentation’ (Reqap) as a method, which is developed on three pedagogical principles: student centered learning, English as a medium of instruction (EMI), and authentic evaluation; (2) the anxiety level the students experienced during the classes using Reqap; and (3) their expectations of Reqap method. The respondents were students of the fifth semester at the English Department of Education and Teacher Training Faculty at Muhammadiyah University of Purwokerto, Indonesia. It randomly took 41 out of 102 students of the semester. This research was descriptive in nature. The data were gathered through closed and open questionnaires. The findings revealed that (1) on average students had good perception of Reqap method (4.02) and (2) the students’ anxiety was at severe level (10.93), and (3) from the open questionnaire the data shows that (a) though it caused the high level of anxiety, the use of EMI brought about awareness in the importance of vocabulary and grammar, (b) authentic evaluation helped create positive backwash on the learning, (c) Reqap made students exerted themselves more, and (d) Reqap facilitated class management. The implications of this study point to the importance of using teaching methods characterized by student centered learning, EMI, and authentic evaluation.